Evaluación del impacto socioambiental y económico en los gestores ambientales artesanales y áreas de intervención del sector Tumbaco y Cumbayá , por la ejecución del proyecto "recolección selectiva e inclusión social - aseo y reciclaje". - Rocano Casa, Paulina Marisol (2013)
The Administration Valle de Tumbaco currently running Project Social Inclusion Selective Collection - Cleaning and Recycling in parishes and Tumbaco Cumbayá, with the aim of raising awareness on good environmental practices (source separation and recycling) parallel with a separate collection of containerization and benefiting from the recovery, processing and marketing of recyclable inorganic waste to 24 environmental managers. The project objective is to know the real socio economic environmental managers, their productive activities and the risks to which they are exposed daily, considering the environmental benefit that managers give the Valley Artisan Tumbaco also the Distrito Metropolitano de Quito while it searches for executables strategize continuous process improvement and individual growth and collective Tumbaco Valley Association (ASOGAV). For the development of this thesis topic was considered the chapters are as follows: Chapter I, describes the objectives of the Thesis Project based on a history of the problem of solid waste and action measures taken by the Zonal Administration Tumbaco in relation to efficient waste management system. Chapter II, says a brief conceptualization of solid waste and the problems presented at the global, national, district and local levels in relation to the generation, collection and disposal of waste. With respect to Chapter III, detailing the production process carried out by environmental managers Valle Tumbaco and potential occupational hazards that are exposed daily for recovery activities inorganic recyclable solid waste.